2022 Joint European Conference on Networks and Communications &Amp; 6G Summit (EuCNC/6G Summit) 2022
DOI: 10.1109/eucnc/6gsummit54941.2022.9815783
|View full text |Cite
|
Sign up to set email alerts
|

6G Radio Requirements to Support Integrated Communication, Localization, and Sensing

Abstract: 6G will be characterized by extreme use cases, not only for communication, but also for localization, and sensing. The use cases can be directly mapped to requirements in terms of standard key performance indicators (KPIs), such as data rate, latency, or localization accuracy. The goal of this paper is to go one step further and map these standard KPIs to requirements on signals, on hardware architectures, and on deployments. Based on this, system solutions can be identified that can support several use cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The needed abstraction levels of RF components' mathematical models depend on modeled impairments and the research problem to which the information is applied. The 6G system and link-level research can use the inventive simulation framework and analyze radio parameters of future 6G networks with more accurate simulation parameters as studies shown for 6G link level [9] or localization analysis [10]. The inventive framework can model different levels of detail: power level analysis, complex number additive nonidealities, and waveform sample analysis, respectively.…”
Section: 6mentioning
confidence: 99%
“…The needed abstraction levels of RF components' mathematical models depend on modeled impairments and the research problem to which the information is applied. The 6G system and link-level research can use the inventive simulation framework and analyze radio parameters of future 6G networks with more accurate simulation parameters as studies shown for 6G link level [9] or localization analysis [10]. The inventive framework can model different levels of detail: power level analysis, complex number additive nonidealities, and waveform sample analysis, respectively.…”
Section: 6mentioning
confidence: 99%
“…For instance, manufacturing and smart cities, as two sub-categories of massive twining, need different accuracy, data rates, latency, update rates, reliability, and availability [18]. A full list of selected use cases and their corresponding performance metrics can be referred to [18], [35], [56], [59], [110], [488], [499]- [502], closely tied to these of upcoming 6G and beyond systems, for which the ultimate goal would be realizing terabit-per-second links and millimeter-level sensing/localization accuracy [110], [503].…”
Section: A Thz-isac Use Cases and Kpismentioning
confidence: 99%
“…Apart from quantum hardware technology using quantum sensors, quantum software technology can also provide enhanced performance in target detection by using quantumenhanced algorithms for classical target detection in complex environments [235]. Since user localisation, navigation, and sensing are important services in future 6G wireless networks [236][237][238], quantum-enhanced radar and lidar technology might play an important role in 6G that can significantly improve positioning accuracy and imaging quality.…”
Section: Quantum Enhanced Localisation and Navigationmentioning
confidence: 99%